Handshake antimicrobial stewardship for adult surgical patients - Abby Kosharek; Elizabeth Neuner; Emily Welch; Spenser January; Alice Bewley; Kevin Hsueh; Sena Sayood (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract